Нові іоноселективні електроди для визначення купруму (ІІ) - Лагановський, А. В.; Кормош, Ж. О.; Парасюк, О. В.; Олексеюк, І. Д.; Laganovsky, A. V.; Kormosh, Zh. O.; Parasyuk, O. V.; Olexeyuk, I. D. (Волинський національний університет імені Лесі Українки, 2008)
На основі Cu2CdGeS4 виготовлено нові Cu2+-селективні електроди. Крутизна електродної функції складає 39–54 мВ/pC у межах визначення Cu2+ 1·10-8–1·10-1 моль/л при рН 3,0–7,0. Електрод апробований як індикаторний при потенціометричному титруванні Cu2+. A new Cu2+-selective electrodes was prepared on the basis of the Cu2CdGeS4. The electrode exhibits the slope of the electrode function 39–54 mV/pC and provides in the determination of 1·10-8−1·10-1 mol/l copper (II) in the pH range 3,0–7,0. The electrode was used for the potentiometric indication of the titration end point in the determination of Cu2+.
The New Ion-Selective Electrodes for Determination of Copper (ІІ).
Keywords: Cu2+-селективний електрод; Cu2CdGeS4; електродна функція; Cu2+-selective electrode; Cu2CdGeS4; electrode slope